EFL-Writing Activities Using WhatsApp Group: Students’ Perceptions during Study from Home - Nur Muthmainnah; Badi'atul Azmina (LET: Linguistics, Literature and English Teaching Journal, 2020)
This research aims to investigate writing activities using the WhatsApp group during the study from home amid the COVID-19 pandemic and students’ perceptions about it. It is a qualitative research, in which the data were analyzed descriptively. This research was carried out at the Sentence-Based Writing class at IAIN Salatiga, Indonesia, in April - June 2020. This research participant involved 30 students. The researchers utilized a questionnaire and documentation for data collection. After conducting the research, the results revealed various students’ perceptions. 63% of the total students possessed a positive perception toward the writing activities using the WhatsApp group, and the rest 37% of students’ preferred face-to-face meetings and perceived writing using WhatsApp group as boring, confusing, and distracting. After analyzing the WhatsApp group activities, at least five writing activities were conducted: sharing and explaining materials, discussing materials, composing sentences, editing sentences, and posting writing products. Thus, this research can definitely provide teachers with knowledge regarding students' perceptions and writing activities carried out in the WhatsApp group.